Assessment of Food Security Status and the Determinants of Food Security in Selected Households from Coastal Area of Noakhali, Bangladesh (Indian Journal of Public Health Research & Development, 2020)
Background: Household food insecurity means that people either do not have access or unable to purchasefood. In either case, they had to suffer from hunger and poverty. Food security is an important determinant tofulfill sustainable development goals. This study aims at determining the food security status and determinantsof food insecurity in selected households from the coastal belt region of the Noakhali district, Bangladesh.Methods: A purposive sampling technique was employed for this cross-sectional study to select households.They were interviewed using a structured questionnaire in order to determine socioeconomic status andnutritional knowledge. Household Food Insecurity Access Scale was used to determine food insecurity.Results: Our study findings indicated that the majority of households (90.33%) were food secure. Thestudy also revealed that the respondent’s level of education, level of nutritional knowledge, and level ofmonthly income are vital variables that have a significant correlation with food security in their households.However, the respondent’s age, gender did not have any significant correlation with food security. Havingpoor nutritional knowledge (OR=1.604, 95% CI=1.1,87.4) and lower-income level (OR= 7.636, 95%CI=1.14-51.18) have significantly increased the risk of food insecurity. Conclusion: Although food securitystatus is satisfactory, policies should be set up to support nutrition education as well as micronutrient intaketo achieve nutritional security.
Keywords: Food Security, Coastal Area, Nutritional Knowledge, Malnutrition